(untitled) (UUM Journal of Legal Studies, 2020)
The significance of this study lies in its proposal to insert an appropriate provision into the Patents Act 1983 to embody the provisions of Article 31bis TRIPS Agreement. The methodology adopted in this study is library-based, and relies extensively on primary sources such as the Paris Convention, TRIPS Agreement and Patents Act 1983. This is further supported through secondary sources such as articles, books, websites and newspaper reports. The research question posed in this study aims to identify the most appropriate provision that should be incorporated into the Patents Act 1983 in addressing the public health flexibilities provided under Article 31bis. The purpose of this study is to demonstrate that Article 31bis is best incorporated into the Patents Act 1983, under the right of the government mechanism rather than through the compulsory license mechanism. Furthermore, the scope of this study is limited to issues that address the abuse of monopoly, granted by the patent system, with respect to the dire needs of the public health. Hence, this paper discusses the mechanisms that address abuse of the patent system under Article 5(A) Paris Convention, Articles 31 and 31bis TRIPS Agreement, the relevant corresponding provisions under the Patents Act 1983, and subsequently formulates new proposed amendments to Section 84 Patents Act 1983 to buttress the public health flexibilities provided under Article 31bis. The outcome of this study proposes that the provisions of Article 31bis should be incorporated into the Patents Act 1983 under the right of the government mechanism, by replacing the current Section 84 Patents Act 1983 with a newly proposed Section 84.